2014
DOI: 10.1016/j.cbi.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Butachlor causes disruption of HPG and HPT axes in adult female rare minnow (Gobiocypris rarus)

Abstract: a b s t r a c tButachlor is a chloroacetamide herbicide widely used in Asia, and may enter the aquatic environment through agricultural application. In this study, plasma VTG and hormone levels (E2, 11-KT, T3 and T4) were determined after the female rare minnow (Gobiocypris rarus) was exposed to butachlor at environmental relevant concentrations (0, 0.1, 1, and 10 lg/L) for 40 days. The mRNA levels of the HPG axisrelated genes (gnrh, era, vtg, star, lhr, 3b-hsd, cyp11a, cyp17, cyp19a and cyp19b), and the HPT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…Also, in contrast to the current results, administration of goitrogen perchlorate led to increasing of hepatocyte lipid accumulation for zebrafish (Schmidt et al, 2012). In the present work, the higher dose for perchlorate (P100) liver histology showed vacuoles between hepatocytes and degeneration in some cells which can be a signs of stress or hormonal disruption (Zhu et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in contrast to the current results, administration of goitrogen perchlorate led to increasing of hepatocyte lipid accumulation for zebrafish (Schmidt et al, 2012). In the present work, the higher dose for perchlorate (P100) liver histology showed vacuoles between hepatocytes and degeneration in some cells which can be a signs of stress or hormonal disruption (Zhu et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in agreement with other studies on mammalian and non-mammalian vertebrates showing that exposure to DEHP results in meiotic arrest in spermatogenesis and production of fewer spermatozoa (Sharpe et al, 1995;Uren-Webster et al, 2010). However, many works have shown that the adverse effects due to exposure to DEHP and butachlor likely occur preferentially via PPAR signalling pathways by oxidative stress in the testis and oestrogen signalling pathways in the liver (Onorato et al, 2008;Uren-Webster et al, 2010;Zhu et al, 2014).…”
Section: Genesupporting
confidence: 92%
“…LC 50 (96 h) of butachlor in fishes has been reported to range from 0.14 to 0.52 mg/L (0.52 mg/L in rainbow trout, Oncorhynchus mykiss (Tomlin, 1994). Many adverse effects of this herbicide on fish species have been reported (Lasheidani et al, 2008;Guo et al, 2010;Tu et al, 2013;Zhu et al, 2014;Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The androgen-mediated decreases in trβ and dio3 expression in ovarian tissue may be indicative of a more feminized profile. For example, exposure to pesticides with known feminizing and TH-related properties have been shown to decrease dio3 transcripts while increasing erα transcripts in various tissues in fish and frogs (butachlor: Zhu et al, 2014;atrazine: Langlois et al, 2010a). In the present study, the expression of erα significantly increased in 5α-DHT and 5β-DHT treated ovary tissues.…”
Section: Discussionmentioning
confidence: 99%